Evidence for altered hepatic matrix degradation in genetic haemochromatosis. Issue 5 (1st May 1998) - George, D K; Ramm, G A; Powell, L W; Fletcher, L M; Walker, N I; Cowley, L L; Crawford, D H G
Abstract : Background —Altered matrix degradation contributes to fibrosis in some liver diseases but the role of matrix degradation in fibrogenesis associated with genetic haemochromatosis has not previously been addressed. Aims —To measure serum concentrations of tissue inhibitor of metalloproteinase 1 (TIMP-1) and matrix metalloproteinases (MMP), MMP-1, MMP-2, and MMP-3 in patients with haemochromatosis and control subjects. Patients —Forty patients with haemochromatosis and 19 healthy control subjects. Ten of the 40 patients were studied before and after venesection therapy. Methods —Serum levels of TIMP-1, MMP-1, MMP-2, and MMP-3 were measured by enzyme immunoassay and correlated to hepatic iron concentration and degree of histological fibrosis. Results —Serum TIMP-1 was increased in patients with haemochromatosis compared with controls (163 (30) versus 123 (28) ng/ml, p<0.0002). Mean serum TIMP-1 concentration of patients with haemochromatosis without fibrosis was significantly higher than in controls (153 (16) versus 123 (28) ng/ml, p=0.03). Serum TIMP-1 concentration correlated with both hepatic iron concentration and hepatic iron index ( r =0.42, p<0.01; r =0.42, p<0.01). Serum MMP-2 concentrations correlated with increasing degree of fibrosis in patients with haemochromatosis ( r =0.38, p=0.01). The mean MMP-1:TIMP-1, MMP-2:TIMP-1 and age/sex matched MMP-3:TIMP-1 ratios were significantly lower in patients with haemochromatosis than controls (0.11 (0.06) versus 0.2 (0.14), p=0.02; 3.32 (0.9) versus 3.91 (0.81), p=0.05; and 0.26 (0.12) versus 0.47 (0.27), p=0.007, respectively). Following venesection, MMP-2 and MMP-3 concentrations increased by 11% (p=0.03) and 19% (p=0.03), respectively. Conclusions —This study provides the first evidence of an alteration in matrix degradation in haemochromatosis that may be a contributing factor to hepatic fibrogenesis in this disease.